Intercomparison between surrogate, explicit, and full treatments of VSL bromine chemistry within the CAM-Chem chemistry-climate model - Fernandez, Rafael Pedro (2021)
Many Chemistry-Climate Models (CCMs) include a simplified treatment of brominated very short-lived (VSLBr) species by assuming CH3Br as a surrogate for VSLBr. However, neglecting a comprehensive treatment of VSLBr in CCMs may yield an unrealistic representation of the associated impacts. Here, we use the Community Atmospheric Model with Chemistry (CAM-Chem) CCM to quantify the tropospheric and stratospheric changes between various VSLBr chemical approaches with increasing degrees of complexity (i.e., surrogate, explicit, and full). Our CAM-Chem results highlight the improved accuracy achieved by considering a detailed treatment of VSLBr photochemistry, including sea-salt aerosol dehalogenation and heterogeneous recycling on ice-crystals. Differences between the full and surrogate schemes maximize in the lowermost stratosphere and midlatitude free troposphere, resulting in a latitudinally dependent reduction of ∼1–7 DU in total ozone column and a ∼5%–15% decrease of the OH/HO2 ratio. We encourage all CCMs to include a complete chemical treatment of VSLBr in the troposphere and stratosphere.